2018
DOI: 10.1016/j.celrep.2017.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Reconstituting Corticostriatal Network on-a-Chip Reveals the Contribution of the Presynaptic Compartment to Huntington’s Disease

Abstract: Huntington's disease (HD), a devastating neurodegenerative disorder, strongly affects the corticostriatal network, but the contribution of pre- and postsynaptic neurons in the first phases of disease is unclear due to difficulties performing early subcellular investigations in vivo. Here, we have developed an on-a-chip approach to reconstitute an HD corticostriatal network in vitro, using microfluidic devices compatible with subcellular resolution. We observed major defects in the different compartments of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
193
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 176 publications
(217 citation statements)
references
References 39 publications
9
193
1
1
Order By: Relevance
“…1A and Movie EV1). The dynamics of vesicles are in agreement with our recent studies using this technology (Virlogeux et al, 2018;Moutaux et al, 2018).…”
Section: Bdnf Transport Is Slowed In Mecp2-deficient Axonssupporting
confidence: 91%
See 2 more Smart Citations
“…1A and Movie EV1). The dynamics of vesicles are in agreement with our recent studies using this technology (Virlogeux et al, 2018;Moutaux et al, 2018).…”
Section: Bdnf Transport Is Slowed In Mecp2-deficient Axonssupporting
confidence: 91%
“…Cortical neurons plated in the first compartment extend axons that connect to striatal dendrites within the synaptic compartment ( Fig. 1A), thus creating an oriented corticostriatal network on-a-chip (Virlogeux et al, 2018). This network reproduces the physiological network as we previously showed that cortical neurons from embryonic day (E)15.5 are enriched in CTIP2/TBR1 neurons that correspond to the deepest layers of the cortex that send axons to the striatum.…”
Section: Bdnf Transport Is Slowed In Mecp2-deficient Axonsmentioning
confidence: 53%
See 1 more Smart Citation
“…When mice begin to exhibit sensory-motor impairment, iSPNs manifest a deficit in corticostriatal synaptic function that is attributable to a reduction in the release of brain derived neurotrophic factor and its activation of postsynaptic tropomyosin receptor kinase B receptors. [16][17][18] This deficit is paralleled by a reduction in dendritic excitability of iSPNs (unpublished observations). As axospinous cortical synapses constitute the principal source of excitatory drive to normally quiescent iSPNs, these changes suggest that the indirect pathway becomes hypoexcitable in the early stages of HD.…”
mentioning
confidence: 78%
“…There are parallels in the evolution of striatal pathology in animal models of HD. When mice begin to exhibit sensory‐motor impairment, iSPNs manifest a deficit in corticostriatal synaptic function that is attributable to a reduction in the release of brain derived neurotrophic factor and its activation of postsynaptic tropomyosin receptor kinase B receptors . This deficit is paralleled by a reduction in dendritic excitability of iSPNs (unpublished observations).…”
mentioning
confidence: 99%